HUBUNGAN PEMBERIAN PENGHARGAAN (REWARD) DENGAN KINERJA PERAWAT DI RAWAT INAP EKSEKUTIF RUMAH SAKIT UMUM DAERAH KABUPATEN JOMBANG TAHUN 2020 - Nungki Liana Sari, S.K.M (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2023)
Nurses are health professionals who provided services in 24 hours, that a decisive role in improved quality of care through result performance has given and reward system it could affected quality of hospital services. Purpose : seen the relationship between given reward and nurse performance at Jombang Distric Hospital. Method: quantitatif studied ; cross sectional studied design ; total sampling technique. Population and sample amounted 30 nurses. Scope of this research in executive inpatient care at Jombang Distric Hospital. Research results with 0,05 sig of Spearman’s rho are : salary p value 0,041; work condition p value 0.273; Interpersonal relationship p value 0.995 ; total extrinsic reward p value 0,054; achievement p value 0.018; self-recognition p value 0.017; the work itself p value 0.012; responsibility p value 0.114, potential development p value 0.054 ; total intrinsic reward p value 0.028. corelation of variables relate to nurses performance at Jombang Distric Hospital are requaire managerial review and evaluation. Conclusion : there is a relationship give rewards and nurse performance. Suggestions : increase the motivation of nurses by include training and simulations relate to nurses and pay attention to remuneration of nurses.